Critical realism as emancipatory action: the case for realistic evaluation in practice development - Wilson, Valerie (Nursing philosophy, 2006)
To provide rigour when preparing a research design, the researcher needs to carefully consider not only the methodology but also the philosophical intent of the study. This, however, is often absent from reported research and provides the reader with little evidence by which to judge the merits of the chosen methodology and its influence on the study. The purpose of this paper is to set out the case for critical realism as a framework to guide appropriate action in practice development and realistic evaluation for understanding the consequences of those actions. It is evident that critical realism and critical social science share common ground. Emancipatory practice development (ePD) is based on the philosophy of critical social science and therefore by virtue is linked to the tenets of critical realism. Until now, the evaluation of ePD programme has been well served by 4th-generation evaluation. However, this paper outlines the need for a different approach to evaluation, one that is based on critical realism, that is concerned with emancipation, and that can be used in the ever-changing environment of clinical practice. Realistic evaluation not only links strongly to ePD programmes, but also serves as the basis for effective research questions that will test the outcomes of the research and inform the transferability of ePD mechanisms into differing contexts.